2004
DOI: 10.1073/pnas.0403336101
|View full text |Cite
|
Sign up to set email alerts
|

The high- and low-affinity receptor binding sites of growth hormone are allosterically coupled

Abstract: Growth hormone regulates its biological properties via a sequential hormone-induced receptor homodimerization mechanism. Using a mutagenesis-scanning analysis of 81 single and 32 pairwise double mutations, we show that the hormone's two spatially distal receptor binding sites (Site1 and Site2) are allosterically coupled. These allosteric effects are focused among a relatively few residues centered around the interaction between Asp-116 of the hormone and Trp-169 of the receptor in Site2. A rearrangement of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…This interpretation extends and strengthens the data we have previously published for hPRL (9). Additionally, Walsh et al (10) have recently described a similar allosteric coupling of the two human growth hormone receptor binding sites in hGH, suggesting that a similar mechanism may govern hGH receptor binding. We have recently identified contiguous residues in hGH (15)-and hPRL (34)-constituting motifs that, when mutated, uncouple sites 1 and 2.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This interpretation extends and strengthens the data we have previously published for hPRL (9). Additionally, Walsh et al (10) have recently described a similar allosteric coupling of the two human growth hormone receptor binding sites in hGH, suggesting that a similar mechanism may govern hGH receptor binding. We have recently identified contiguous residues in hGH (15)-and hPRL (34)-constituting motifs that, when mutated, uncouple sites 1 and 2.…”
Section: Discussionsupporting
confidence: 73%
“…Previous surface plasmon resonance and Förster resonance energy transfer (FRET) data from our laboratory indicated that receptor binding induced a conformation change in the hormone associated with a functional coupling of sites1 and 2 (9). The observation that hPRL undergoes a conformational change upon receptor binding is consistent with observations of hGH or hPL binding the extracellular domain of the hPRL receptor (10,11) or when hGH binds the extracellular domain of the hGH receptor (12,13). The idea that the receptor binding events are functionally coupled also is consistent with the positive 1.7 Hill coefficient described by Hooper et al (3) in a heterologous ovine PRL/rat PRL receptor system.…”
supporting
confidence: 76%
“…However, no detailed molecular mechanism was formulated, and the extent to which PRL actually undergoes significant structural rearrangements when interacting with the receptor chain via BS1 has been a matter of some debate. In the GH system, it has been demonstrated that BS1 and BS2 are allosterically coupled in the sense that mutations in BS1 can induce conformational changes in BS2 (35). The recent publication of the crystal structure of the PRLR antagonist, PRLv3 (16), in combination with the present determination of the receptor-complexed structure of the closely related variant, PRLv2, provides a unique opportunity to scrutinize the structural rearrangements associated with receptor binding at BS1.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor homodimerization by the human growth hormone (hGH) has been shown to be allosterically regulated (37) and may represent an intermediate on such a continuum. The binding of the two receptor molecules to hGH occurs in a regulated and sequential manner.…”
Section: The Protein Core As a Potential Regulator Of Cooperativity Bmentioning
confidence: 99%